Overview of knowledge about basic life support of nursing students level 3 STIKes Santa Elisabeth Medan - Barus, Mardiati; Sinurat, Samfriati; Stefhanie, Ruth May (International Journal of Nursing and Midwifery Research, 2023)
Basic life support is carried out properly if the rescuer has adequate knowledge and skills in carrying out assistance in maintaining a person's condition during an emergency. Knowledge of basic life support must be possessed by every health student who will become a nurse at the forefront who will carry out basic life support properly and appropriately later. Basic life support is a form of emergency first aid given to maintain and provide support in the form of circulation, airway, and breathing. The purpose of this study was to describe Knowledge About Basic Life Support of Nursing Students level 3 STIKes Santa Elisabeth Medan. This research uses descriptive research method, total sampling with a sample of 85 respondents. The measuring instrument used is the Basic Life Support Knowledge questionnaire. The results showed that the majority of respondents had sufficient knowledge of basic life support as many as 61 respondents (71.8%) and basic life support knowledge was good for the minority as many as 24 respondents (28.2%). It is hoped that with the results of this study, respondents will try to improve their knowledge well from receiving learning from lectures, attending seminars and workshops on basic life support as the main basis for the respondent's duties as prospective nurses.